ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA CAFÉ HAAGENDAZS BEACHWALK KUTA - Ida Ayu Trisna Wijayanthi; Desak Made Handewi Dyah Savitri (JURNAL STIE SEMARANG, 2021)
The right marketing strategy will create opportunities for the company to get higher profits, which means it will increase the company's prosperity. For this reason, it is necessary to implement effective marketing strategies in developing companies. One of the developing companies in Bali is PT. Rahayu Arumdhani International, where they are the main distributor of Haagendazs ice cream products in Bali and manage Haagendazs cafes in Indonesia, one of which is Haagendazs café in Bali, namely Haagendazs Beachwalk Kuta. Café Haagendazs Beachwalk Kuta has a very high sales target, where this target will increase by 5% from reality every year, based on the company's historical sales data. The purpose of this study is to describe and analyze effective marketing strategies in increasing sales volume at the Haagendazs Beachwalk Kuta café which can be applied during the new normal from the Covid-19 pandemic using the SWOT analysis method. The results showed that Café Haagendazs Beachwalk Kuta is a company that implements a marketing strategy that differentiates the market (differentiated marketing) with the type of entrepreneur who segments the market, applies the 4P marketing mix concept to its daily marketing activities. The results also show that to increase the effective sales volume the company must use and implement an aggressive growth strategy, namely by developing and exploiting the strengths and opportunities (SO) owned by Café Haagendazs Beachwalk Kuta for business development.